Macroenzymes as a reason for aminotransferases flare in cystic fibrosis patients on CFTR modulators therapy – Report of three cases - Woynarowski, Marek; Sapiejka, Ewa; Jóźwiak, Maria; Milczewska, Justyna; Zybert, Katarzyna; Krusiński, Adam; Siwiec, Jan; Wierzbicka-Rucińska, Aldona (Heliyon, 2024)
It has been shown that macro-ALT/macro-AST cause false increase of ALT/AST activity in standard laboratory testing. This short communication presents a group of cystic fibrosis subjects who developed aminotranferases flare a few months after initiation of CFTR modulators therapy. Patients did not present any clinical signs or symptoms of liver failure and differential examination did not show any underlying liver disease. All patients tested positive for macro-ALT and macro-AST. Despite increased and fluctuating ALT/AST activity in standard tests patients restarted CFTR modulators therapy with good clinical effect and do not present any other than hypertransaminasemia signs or symptoms of progressing liver disease. Our data shows that ALT/AST flare during CFTR modulators therapy may be related to macro-ALT/macro-AST, thus patients with high ALT/AST during CFTR modulators therapy should be tested for macro-ALT/macro-AST.